PENGARUH RASIO KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE DI BEI - Khoirul Hanif, Abdul Wahab; Wijayanti, Anita; Masitoh, Endang; Samrotun, Yuli Chomsatu (Universitas Slamet Riyadi, 2019)
This study aims to discuss the financial ratios and corporate governance to the value of the company. This analysis uses veriabel independent financial ratios (liquidity and leverage) and corporate governance (institutional ownership and company size). The dependent variable is firm value. The population of this study is the food and beverage companies listed on the Indonesia Stock Exchange for the period 2013 – 2017. The research sample was selected using the purpose sampling and statistical methods using multiple linear analysis. There are 11 companies that meet the criteria with a period of 5 years producing 55 samples. The results showed that institutional ownership and firm size affect firm value, while liquidity and leverage do not affect firm value.